PENGEMBANGAN BAHAN AJAR SASTRA ANAK BERBASIS LOKAL DAN BERPIKIR KREATIF SISWA - Alim, Abdul; Nahdi, Khirjan; Nursaly, Baiq Rismarini (Universitas Hamzanwadi, 2022)
This study aims to develop local-based children's literature teaching materials and students' creative thinking skills and to describe creative thinking skills through local wisdom-based on children's literature teaching materials. This research is a development research. This study develpos the of children's literature teaching materials based on local wisdom and creative thinking that is adopted from the ADDIE development model which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The study was carried out on a small scale and a large scale by conducting validation first, namely: 1) linguist validation, the score obtained was 26 in the interval (23 < X (29) with the category